Death-Related Conversational Implicature in Genshin Impact: A Pragmatic Analysis of Hu Tao's Character Dialogue in the Papilio Charontis Story Quest - Muhamad Rizky Ramadhan; Deni Suswanto; Toneng Listiani (Journal of English Language and Education, 2026)
Death is a sensitive topic commonly expressed through indirect language such as euphemism, metaphor, and irony, yet how conversational implicature systematically conveys death-related meanings within a single character's discourse in interactive digital narrative remains theoretically unaddressed. This study examines how death-related conversational implicatures are realized in Hu Tao's dialogue in the Papilio Charontis story quest of Genshin Impact, which Gricean maxims are flouted to generate them, and how these implicatures convey indirect references to death. Employing a qualitative descriptive approach grounded in Grice's (1975) Cooperative Principle, data were collected through document analysis of the quest transcript and analyzed by identifying indirect expressions, determining maxim violations, and interpreting death-related meanings through pragmatic inference. The analysis of 33 utterances reveals that metaphorical expression, euphemism, and irony are the dominant strategies, with the maxim of manner most frequently flouted, and 32 of 33 implicatures classified as particularized. The findings confirm that Grice's framework is applicable to interactive digital narratives and that conversational implicature functions as a core mechanism of character identity construction in video game discourse.